Studies on the C2-deficiency gene in man. - Mortensen, J P (1980)
A one-step haemolytic assay using cellular intermediates was used to determine C2 levels in 50 HLA-A25 and B18 positive blood donors and four families suspected to have the C2-deficiency gene. The method clearly discriminated between homozygous normals and heterozygous deficient individuals, and it was found that approx. 50% of individuals with the haplotype HLA-A25, B18 had low levels of functional C2. In the four families studied, the close linkage of the C2-deficiency gene and the haplotype HLA-A25, B18 was confirmed. Furthermore, the C2-deficiency gene was shown to be a silent or null allele at the structural locus.